The Use of Cooperative Integrated Reading and Composition (CIRC) Method in Improving Writing Ability of Narrative Text of the Second Year Students of SMAN 4 Pekanbaru - Desi Nurista Nurista; Rumiri '; Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This classroom action research was aimed to find out if the use of Cooperative Integrated Reading and Composition (CIRC) Method could improve the writing ability of the second year students of SMAN 4 Pekanbaru. The participants were 31 students. The procedures applied were: (a) dividing students into pairs, (b) asking students to read to each other the story, (c) asking students to correct their teammates’ error, (d) asking students to answer the questions related to the story in team, (e) asking students to pronounce the difficult words listing, (f) asking students to find the meaning of the difficult words listing, (g) asking students to write a draft composition of narrative texts related to the passage, (h) asking students to edit one’s another’s work by using peer editing, (i) asking students to finish their writing based on their teammates’ revision. The data was collected by using of tests, observation sheets, and field notes. The level of achievement in this research was 85, based on the standard minimum criteria of achievement of English subject in SMAN 4 Pekanbaru. The research finding showed that the implementation of applying CIRC as the teaching method could improve students’ writing ability both at the first, second, and third cycle. Based on the data analysis that is obtained, the students’ score was improve from 60,32 in the pre-test, to 74,62 in post-test 1, to 83,29 in post-test 2, and up to 87,68 in post-test 3. Therefore, the implementation of CIRC method could improve students’ writing ability of the second year students of SMAN 4 Pekanbaru. Keywords: CIRC Method , Writing Ability, Narrative Text